Role of low dose ecosprin and heparin in achieving live births in pregnancy with thrombophilia - Asthana, Shilpa; Sodhi, Bandana; Kumar, Satish (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Thrombophilia is a disorder of haemostatic system that results in increased tendency of thrombus formation in both venous and arterial vascular system. The thrombotic events are not only restricted to venous thromboembolism but also can cause fetal loss (abortions or recurrent abortions and fetal demise), placental abruption, intrauterine growth restriction and severe pre-eclampsia. This study evaluates the role of administering thromboprophylaxis with heparin and ecosprin to patients with thrombophilia in pregnancy with previous history of adverse obstetric outcomes. Methods: This prospective study was conducted in 60 patients diagnosed with thrombophilia during pregnancy. The objective of the study was to determine the role of administering low dose ecosprin and heparin as thromboprophylaxis in achieving live births in these patients with thrombophilia. All patients included in this study were prophylactically administered low dose ecosprin with either unfractionated heparin (5000 IU s.c, BD) or low molecular weight heparin (40 mg s.c, OD) during pregnancy. Patients were followed up in the antenatal period and the obstetric outcome noted. Comparisons were made between the obstetric outcomes of these patients receiving the aforesaid thromboprophylaxis with those of previous untreated pregnancies during which no ecosprin or heparin had been administered. The data obtained were subjected to statistical analysis using Students ‘t’ test and Chi square analysis. P value <0.05 was considered statistically significant. Results: Fifty nine of the sixty patients with thrombophilia and previous adverse pregnancy outcome who received prophylaxis with ecosprin and heparin during the present pregnancy had live births (98.33%; p <0.0001). Fifty-eight (96.66%) of these patients progressed to term delivery and one (1.67%) pregnancy resulted in a pre-term birth. Conclusions: Present study reveals that prophylaxis with low dose ecosprin and heparin administered to patients with thrombophilia (acquired or inherited) with history of previous adverse obstetric outcome resulted in a positive outcome in terms of a significantly higher number of live births. However, larger studies are needed to further elaborate on the role of thromboprophylaxis in pregnancies with inherited thrombophilia.